Salinazinones A and B: Pyrrolidinyl-Oxazinones from Solar Saltern-Derived Streptomyces sp KMF-004 - Kim, Min Cheol; Lee, Jung Hwan; Shin, Bora; Subedi, Lalita; Cha, Jin Wook; Park, Jin-Soo; Oh, Dong-Chan; Kim, Sun Yeou; Kwon, Hak Cheol (AMER CHEMICAL SOC, 2015)
Salinazinones A (1) and B (2), two unprecedented pyrrolidinyl-oxazinones, were isolated from the culture broth of Streptomyces sp. KMF-004 from a solar saltern at Aphae Island, Korea. The structures of these salinazinones, which are unusual and consist of 2-methylpropenyl-1,3-oxazin-6-one bearing 1-oxopyrrolidinyl substituents, were assigned by spectral and chemical analyses using Mosher's method, circular dichroism (CD), and calculated ECD. Salinazinones are the first examples of a natural alkaloid class composed of an oxazinone-pyrrolidone conjugate.
Keywords: DERIVATIVES; ASSIGNMENT